(untitled) (Journal of Hama University, 2021)
Aims and Objectives:The aim of this laboratory study was to evaluate the effect of Er:YAG laser compared to the traditional method (Diomand burs with mechincal handpiece), used for apiectomoy , on the sealing ability of two Bio-Stimulating Materials [Biodentine –Endo Sequence Root Repair Material (ERRM)] used as retrogtrade fillings.Materials and Methods:fifty extracted single rooted teeth were selected with completed, straight and single canal root and free of caries , resorption or previous treatment. The teeth crowns were removed and root length was adjusted to 14mm. Teeth were devided into 5 groups of 10 teeth each. Group I: Diomand burs used for apicetomoy -Biodentine used for retrofilling.Group II: Diomand burs used for apicetomoy -ERRM used for retrofilling.Group III:Er:YAG laser used for apicetomoy -Biodentine used for retrofilling.Group IV:Er:YAG lasr used for apicetomoy -ERRM used for retrofilling.Group V:(control Group) Diomand burs used for apicetomoy -no retofilling.retrograde cavities were made using ultrasonic tips.nail polish were applied to all teeth surfaces after placing the retrofilling materials expect the apical surface , teeth emerged in methylene blue paint for 24 hours.vertical sections were maed and then teeth were examined using microscope to determine the level of leakage .Mann Whitney test was used to show the difference in micro leakage level between the two methods used in apiectomy and the two retorgade fillings used. All stastical analysis was performed at 95% level of confidence. The results showed stastically significant differences in apical leakage regarding apex section using laser Er:YAG compared to Tradional methond(Diamond burs), and showed no stastically significant differences between the two retrograde fillings. conclusion: Apiectomoy using Er:YAG laser provides better sealing ability than traditional method ,whereas Biodentine and ERRM shows the same sealing ability in both methods used.